071 Quality of life in patients with chronic heart failure and their carers: a 3-year follow-up study assessing hospitalisation and mortality. (22nd September 2015) - Iqbal, J; Francis, L; Reid, J; Murray, S; Denvir, MA
Abstract : Introduction: Chronic Heart Failure (CHF) due to left ventricular systolic dysfunction is associated with poor quality of life (QoL) and survival. This study aimed to assess the effects of a wide range of clinical, social, psychological and demographic factors on QoL in an unselected cohort of CHF patients and their carers and to investigate the impact of QoL on subsequent hospitalisation and mortality. Methods: Demographic, social and clinical data were collected for consecutive CHF patients in an academic hospital setting. All patients (n=179) and informal carers (n=131) completed a generic QoL questionnaire (EQ-5D) and patients also completed CHF specific QoL questionnaire (Minnesota Living with Heart Failure, MLHF). Patients were then followed up for 3 years to assess subsequent hospitalisations and mortality. Data were analysed employing step-wise multiple regression and Cox proportional-hazards survival model. Results: CHF patients had poor QoL with a mean QoL score of 50±2 on MLHF questionnaire and 0.57±0.03 on EQ-5D questionnaire. QoL score was independently predicted by NYHA class (p<0.001), socioeconomic deprivation (p<0.001) and lack of an informal carer (p=0.05). QoL of carers was associated with QoL of patients and was particularly low in female carers compared to male carers (0.74±0.02 vs 0.86±0.05, p=0.03). Moreover, carer QoL was also affected by patient related factors including NYHA class, presence of anaemia or a cancer. During the follow-up period of 3 years (range 33–40 months), 67 patients (37%) died. CHF patients in lowest QoL quartile were at significantly increased risk of hospital admissions (HR 7.3, 95%CI 3.6 to 9.1, p<0.001) and death (HR 1.7, 95%CI 1.1 to to 2.9, p=0.03). Mortality was also independently associated with multiple hospitalisations (HR 6.0, CI 3.3 to to 10.0, p<0.001) and lack of β-blocker therapy (HR 1.8, CI 1.1 to 2.8, p=0.03). Conclusion: Severe heart failure, poor socioeconomic status and lack of social support results in poor QoL in CHF patients which in turn leads to an increased risk of hospital admissions and death. Clinical Implications: QoL assessment may complement clinical prognostic markers to identify CHF patients at high risk of adverse events. Serial assessment of QoL may also provide additional valuable information about disease progression, effect of interventions and prognosis.